TAHAPAN PERKEMBANGAN BAHASA ANAK USIA 4-5 TAHUN DALAM PERSPEKTIF ALIRAN STRUKTURALISME: STUDI KASUS DI KB LARAS SAKTI - Dhea Yunika; Meta Rosalia; Rosalina Destyaningsi; Syaza Aulia Alpinia; Novita Loka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Language development in children aged 4–5 years forms a critical foundation for cognitive, social, emotional, and academic growth. However, challenges such as delayed articulation, limited vocabulary, and difficulties in constructing sentences remain prevalent. This study aims to comprehensively analyze language development in this age group through a structuralist lens encompassing phonology, morphology, syntax, and semantics simultaneously an innovation over prior studies that addressed only one or two linguistic components. A qualitative case study design was employed at KB Laras Sakti Sakatiga. Data were collected through observations during animal-habitat-themed learning activities, guided question-and-answer sessions, and field documentation using observation sheets and interview guides. Data analysis was organized according to relational language patterns observed in child interactions. Findings indicate that children could follow simple instructions, respond to questions about animal habitats, produce vocabulary such as bird, fish, and water, and construct basic sentences like